Estudo do ergodesign nas escolas estaduais da cidade de Bauru (SP): reavaliação dos espaços e dos mobiliários - Caversan, Adriana Lima [UNESP] (2014)
This research analyzes through observation of environmental elements, the physical postures adopted by people in schools and lay outs found in the chassrooms studied. It was performed on eight different public state schools in the city f Bauru - SP in the first years of elementary school students from first to fifth years with estimated age between six and years old. The decision to select these eight schools was due to the fact that in 2008 they were the subject of research in the Graduate Program in Design - UNESP - Bauru. This research therefore follows the previous one deepening the studies in lay out spaces and postures. The research involved the participation of 708 students and the collaboration of 34 teachers who agreed on the collection of data being held in their classrooms. It presents historical approach to literature review of school furniture and its spaces, to reach contemporary solutions of spatial arrangements and innovative furniture that are based on ergonomic studies focused on children. The analysis of spaces present an overview of the schools studied, goes through classrooms and their physical restraints. In the sequel there is the direct observation of children using desks and spaces including the Lay outs found, observing the concepts of technical manuals and books and using studies of child anthropometry, an analysis of postures commonly adopted by children is made when they are using school desks